Gender implications of biofuels expansion: A CGE analysis for Mozambique - Channing Arndt; Rui Benfica; James Thurlow (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
We use a gendered computable general equilibrium model to assess the implications of biofuels expansion in Mozambique. We compare scenarios with different gender employment intensities in producing jatropha for biodiesel. Under all scenarios, biofuels accelerate GDP growth and reduce poverty. However, a stronger tradeoff between biofuels and food availability emerges when female labour is used intensively, as women are drawn away from food production. A skills-shortage amongst female workers also limits poverty reduction. Policy simulations indicate that only modest improvements in women's education and food crop yields are needed to address food security concerns and ensure broader-based benefits from biofuels.
Keywords: O13; O55; I3; J16; 330; Biofuels; gender; poverty; growth; Africa; Biokraftstoff; Geschlecht; CGE-Modelling; Allgemeines Gleichgewicht; Mosambik